Five Nights at Freddy's : Fazbear Frights - Vol 5 Vol. 5 - Cawthon, Scott, 1971-; Cooper, Elley; Waggener, Andrea Rains, 1960-; Camero, Diana; MacPherson, Coryn; Sawyer, Benjamin; Lai, Judy; Duarte, Gonzalo (Colorist); De la Cruz, Eva; Esposito, Taylor (New York, NY : Graphix, an imprint of Scholastic, 2024)
"Frustrated by an unfair arcade game, Colton throws himself into re-engineering the device at any cost. Mott quickly flushes his brothers creepy new pets down the drain, but the creatures have other plans. Aimee finally works up the courage to ditch her loud-mouthed, annoying friend at Freddy Fazbears Pizza. But when it comes to Five Nights at Freddys, even the most ordinary seeming actions can reap horrible consequences"--Back cover.
illustrated by Ben Sawyer ; colors by Eva de la Cruz?.
"Teen, ages 12 and up"--Back cover.
Keywords: Robotics -- Comic books, strips, etc; Robotics -- Juvenile fiction; Survival -- Comic books, strips, etc; Survival -- Juvenile fiction; Murder -- Comic books, strips, etc; Murder -- Juvenile fiction; Robotics -- Fiction; Survival -- Fiction; Murder -- Fiction; Graphic novels; Horror comics; Comics adaptations; Comics (Graphic works)